Characterization Of Spatial Variability Of Soil Nutrients At Seberang Perai, Malaysia - Lai, Kong Soon (Universiti Sains Malaysia, 2005)
This study addressed the characterization of spatial variability of soil nutrients at Seberang Perai, Malaysia using Geostatistical methods. Accurate information from this study on the spatial variability of soil chemical properties is very important in understanding and characterization of small scale spatial variability nature of nutrient properties of tropical soil, and thus allows in investigation of the catchment’s characteristics in Seberang Perai area in Malaysia. Two significant aspects of spatial variability of soil chemical properties were examined in this study. First, spatial distribution patterns of soil chemical properties (pH, total Nitrogen (N), available Phosphorus (P) and exchangeable Potassium (K)) were investigated and secondly the spatial autocorrelation for these properties were investigated. The study area was divided by a number of geo-grid reference points. Soil samples (n=70) were collected at these points and were analyzed in the laboratory for soil chemical soil properties. Differential global positioning system (DGPS) was used to locate the sample position. These soil properties along with their geo-grid reference location were analyzed to produce soil properties map over the entire area using the software SURFER. Semivariogram analysis was performed for the spatial soil properties to examine the autocorrelation among the data set using GS+ software. Results indicate that significant spatial variability exist in the soil chemical properties. The nugget to sill ratio indicates a moderate dependency for soil pH and available Phosphorus, while a strong dependency for Potassium and total Nitrogen.